IMPLEMENTASI PROGRAM TAHFIDZ ‎LEMBAGA MADRASAH HIFDZIL QUR’AN ‎DALAM MENINGKATKAN KUALITAS ‎HAFALAN SANTRI ‎ ‎(Studi Kasus di Pondok Pesantren Putri Walisongo ‎Cukir Jombang)‎ - Nabitatul Mawaddah; Said, Ali (PAI FAI UNHASY Tebuireng Jombang, 2022)
The Hifdzil Qur'an Madrasah Institution is a Qur'an memorizing unit under the auspices of the Putri Walisongo Islamic Boarding School. This institution implements a tahfidz program that will support students in the memorization process and help improve the quality of students' memorization. Jombang). This study aims to (1) describe and analyze the quality of student memorization at the Madrasah Hifdzil Qur'an (MHQ) Pondok Pesantren Putri Walisongo (2) to describeethe implementation of the tahfidz program at Madrasah Hifdzil Qur'an (MHQ) institutions in improving the quality of memorization. female Islamic boarding school students Walisongo (3) describe and analyze the factors supporting and inhibiting the implementation of the tahfidz program at the Islamic boarding school Hifdzil qur'an (MHQ) in improving the quality of memorization of the Walisongo IslamicBoarding School. This research is included in qualitative research using data collection techniques by means of interviews, documentation, and observation, the type of research used is a case study. The data analysis technique uses Sugiono's theory in the form of data reduction, ddata presentation and data verification/withdrawal. Techniques for checking the validity of the data using credibility tests include extending participation, increasing observation persistence and triangulationntechniques. Therresults of this study are the implementation of the tahfidz program at the MHQ institution in the form of muroja'ah, talaqqi, fashoha, tasmi', bin-nazdhar, monthly and semester exams. The program is very effective